Using technology to support high-impact educational practice - Ivers, Karen S. (Libraries Unlimited, an Imprint of ABC-CLIO, LLC, 2019)
"Emphasizing the importance of preparing students for the global workforce, this title explains how to teach using the latest educational technology"--